Single telomere length analysis in Ustilago maydis, a high-resolution tool for examining fungal telomere length distribution and C-strand 5’-end processing - Ganduri Swapna; Eun Young Yu; Neal F. Lue (Microbial Cell)
Telomeres play important roles in genome stability and cell proliferation. Telomere lengths are heterogeneous and because just a few abnormal telomeres are sufficient to trigger significant cellular response, it is informative to have accurate assays that reveal not only average telomere lengths, but also the distribution of the longest and shortest telomeres in a given sample. Herein we report for the first time, the development of single telomere length analysis (STELA)—a PCR-based assay that amplifies multiple, individual telomeres— for Ustilago maydis, a basidiomycete fungus. Compared to the standard telomere Southern technique, STELA revealed a broader distribution of telomere size as well as the existence of relatively short telomeres in wild type cells. When applied to blm∆, a mutant thought to be defective in telomere replication, STELA revealed preferential loss of long telomeres, whose maintenance may thus be especially dependent upon efficient replication. In comparison to blm∆, the trt1∆ (telomerase null) mutant exhibited greater erosion of short telomeres, consistent with a special role for telomerase in re-lengthening extra-short telomeres. We also used STELA to characterize the 5’ ends of telomere C-strand, and found that in U. maydis, they terminate preferentially at selected nucleotide positions within the telomere repeat. Deleting trt1 altered the 5’-end distributions, suggesting that telomerase may directly or indirectly modulate C-strand 5’ end formation. These findings illustrate the utility of STELA as well as the strengths of U. maydis as a model system for telomere research.